1998
DOI: 10.1183/09031936.98.11020440
|View full text |Cite
|
Sign up to set email alerts
|

Time course of pulmonary artery pressure during sleep in sleep apnoea syndrome: role of recurrent apnoeas

Abstract: The increase in pulmonary arterial pressure (Ppa) during acute hypoxia is mainly related to alveolar hypoxaemia inducing vasoconstriction of precapillary pulmonary arterioles [1,2] whereas during chronic hypoxia, mechanical and hormonal factors make the vessels adapt to hypoxia and modify their response to chemical stimulus [3]. Furthermore, the temporal profile of the hypoxaemic stimulus may have a substantial effect on the pulmonary vascular response [4] as suggested by experimental studies allowing that rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
1
12
1
Order By: Relevance
“…Whereas normal subjects exhibited only slight changes in P PA (4)(5) with no variation during the different stages of sleep (998), patients with OSA exhibited large swings in P PA during apneic events, and a generally progressive increase in P PA overnight (232,1185,1534,1751) with systolic P PA often reaching 50 -60 mmHg (232,1388,1909). Although some studies found no correlation between sleep stage and severity of pulmonary hypertension (1751), most found that extreme increases in P PA tended to occur during periods of rapid-eye-movement (REM) sleep (321,1388,1720,1841), probably because airway obstruction and arterial O 2 desaturation were most severe during this time (321,1186,1720).…”
Section: Sleep-disordered Breathingmentioning
confidence: 96%
“…Whereas normal subjects exhibited only slight changes in P PA (4)(5) with no variation during the different stages of sleep (998), patients with OSA exhibited large swings in P PA during apneic events, and a generally progressive increase in P PA overnight (232,1185,1534,1751) with systolic P PA often reaching 50 -60 mmHg (232,1388,1909). Although some studies found no correlation between sleep stage and severity of pulmonary hypertension (1751), most found that extreme increases in P PA tended to occur during periods of rapid-eye-movement (REM) sleep (321,1388,1720,1841), probably because airway obstruction and arterial O 2 desaturation were most severe during this time (321,1186,1720).…”
Section: Sleep-disordered Breathingmentioning
confidence: 96%
“…The mean increase in pulmonary artery pressure was about 10 mm Hg, observed toward the end of an apneic episode, although no evidence of a progressively increased pulmonary artery pressure throughout the night was seen. However, other researchers have reported a small increase in pulmonary artery pressure throughout the night of about 0.5 mm Hg/hour of sleep in patients with OSA [51] (class III). Taken together, these studies suggest that elevated pulmonary artery pressure in the setting of OSA likely is the result of a combination of mechanical effects, a short-term hypoxic vasoconstrictive effect, and perhaps subacute effects leading to progressively higher pulmonary artery pressures.…”
Section: Continuous Positive Airway Pressurementioning
confidence: 85%
“…The mPAP in our study was ∼40 mmHg, whereas it is usually in the 20s in patients with PH secondary to OSA. [3][4][5][6][7][8][9] Severe PH (mPAP > 40 mmHg) is rare in patients with OSA. A recent study of patients with OSA reported severe PH in 8 (44%) of the 18 patients with PAH in that study.…”
Section: Discussionmentioning
confidence: 99%